Peran Notaris Dalam Membuat Akad Pembiayaan Murobahah Di Bmt Maslahah Cabang Besuk Pasar Senen - Fadila, Nurul; Hakim, Ahmad Faizul (universitas Islam Zainul Hasan Genggong, 2023)
A notary is an official appointed by the Government and has the authority to carry out authentic deeds. Sharia contracts that are notarized to qualify as genuine instruments must comply with applicable laws and regulations. Therefore, the Notary when making a sharia contract deed is obliged to pay attention to the provisions of sharia law. The position of a notary and sharia principles are stated in the contract. One form of sharia contract that is widely used in BMT cooperatives is the murabahah contract. The purpose of this article is to explore and analyze the murabahah contract and the role of the notary in signing the murabahah financing contract deed at the BMT Cooperative. The method used in this article is the empirical legal method, which is described specifically with primary and secondary data and analyzed qualitatively. This article produces: (1) Murabahah financing contract is an agreement that is in accordance with sharia principles regarding the sale and purchase of goods with a medium of exchange accompanied by predetermined additions and (2) Notary is a public official who has the right to do so. authentic deed, considering how important the authority and role of the Notary is, the Notary must have extensive knowledge or understanding, one of which is related to the technique of executing the deed that will be carried out later. It is important for Notaries to understand the principles of sharia law, especially the principle that all their activities are based on Islamic law.